Urinary guide-wire and Tritube solved the mystery of severe tracheal stenosis management: A case report - Muhammad Firas., Alhammad (2023)
Patients with tracheal stenosis may exhibit various signs and symptoms of respiratory compromise, depending on the degree of stenosis. Proper identification and prompt intervention are crucial to ensure the best possible outcomes for patients with tracheal stenosis.We present a case of a woman scheduled for an elective gynaecological surgery under general anaesthesia, where the ordinary tracheal tube was unable to progress in spite of Cormack-Lehane Grade I during direct laryngoscopy" The patient's medical history revealed that they had undergone endotracheal intubation during childhood for unknown reasons. The patient had a skin scar on the front of her neck and a hoarseness of voice since childhood. This case underscores the importance of a thorough medical history and physical examination in identifying and managing conditions such as a tracheal stenosis, which might go unnoticed and pose a significant risk to patient health.The successful intubation was achieved using a straw size tube, (Tritube)®, with a small ID of 2.4 mm and an OD of 4.4 mm. The Tritube was inserted over a urinary guide wire and assisted with a fibreoptic scope and video-laryngoscope with a D blade. Despite the complexities of the situation the patient's airway was secured successfully in a timely manner.A neck scar should serve as a red flag for healthcare professionals to conduct further investigations into a patient's airway, even if the patient appears to be in good health.